6x+3=5-2(4+-1)

Simple and best practice solution for 6x+3=5-2(4+-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+3=5-2(4+-1) equation:


Simplifying
6x + 3 = 5 + -2(4 + -1)

Reorder the terms:
3 + 6x = 5 + -2(4 + -1)

Combine like terms: 4 + -1 = 3
3 + 6x = 5 + -2(3)

Multiply -2 * 3
3 + 6x = 5 + -6

Combine like terms: 5 + -6 = -1
3 + 6x = -1

Solving
3 + 6x = -1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 6x = -1 + -3

Combine like terms: 3 + -3 = 0
0 + 6x = -1 + -3
6x = -1 + -3

Combine like terms: -1 + -3 = -4
6x = -4

Divide each side by '6'.
x = -0.6666666667

Simplifying
x = -0.6666666667

See similar equations:

| x^2+12x+6=-5 | | 4y=2y+18 | | y=0.4x^2+5.4x+14.8 | | x^2-11001x-462000=0 | | c^2-9c+8= | | X^2-kx+36=0 | | m^2-m=0 | | 5-8x=86-29x | | -23-6x=8x+24 | | 9x-3=16x-43 | | 0.03p-0.12=-0.01p | | 80=3a+2y | | -3.9x-1=-3.7x+3 | | 5d^2-100=0 | | 2n+3.6=6.8 | | x^2+49-49=0 | | 3n+3.5=7.7 | | -36+16=-3x+7x | | 2x^3-3x^2*a-a^3=0 | | x^4-4x^4-5=0 | | 5(5x+8)=240 | | 0.4-18=3n-16-0.8n | | 2y+2=3+2y | | 85-25a=19 | | .25x+.75x=0-x | | 2x^2-12=x^2-6 | | 3(x+2)=5(x+2) | | .20(4x+3)=7 | | 16(p-1)=p(p+8) | | .25(4x+12)=x+3 | | 6x+19-2x=x+16 | | 8(t-4)+4t=4(3t+3)-11 |

Equations solver categories